Otis-Lennon School Ability Test, Association of Benedictine Schools Achievement Test, and National Achievement Test as Correlates of Academic Performance - Santillan Jr., Eduardo P. (Future Science / FSH-PH Publications, 2023)
Believing that students take several tests whose results help describe these learners, the researcher measured the correlation between the academic performance (AP) and Otis-Lennon School Ability Test (OLSAT), AP and Association of Benedictine Schools Achievement Test (ABSAT), and AP and National Achievement Test (NAT), OLSAT and ABSAT, OLSAT and NAT, and ABSAT and NAT scores of the grade 6 students of a private school in Angeles City. This is a descriptive correlational study. Using frequency and percentage, the researcher described the results of the given standardized tests and the pupils’ academic performance using general weighted average. Using descriptive statistics, the researcher learned that participants had average performance in AP and the specified tests. Using Pearson r, the researcher learned that all variables registered positive results, particularly average performance. Thus, the study arrived at significant relationships between participants’ academic performance and the named tests. The study also revealed significant relationships between participants’ AP and the tests, between OLSAT and NAT, between ABSAT and OLSAT, and between ABSAT and NAT. The study implies that the school must maintain its good teaching and learning practices and innovate to capitalize and improve general performance.